Communism Debated Again: The Muslim Response to the Idea of Revoking the 1966 anti-Communism in Post-Soeharto Indonesia - Suhelmi, Ahmad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
This article analyses the responses of the Muslim political elite to President Abdurrahman Wahid's proposal of revoking MPRS Decree No. XXV/1966, which sought to stifle the spread of Communism and the Indonesian Communist Party (PKI). The proposal provoked controversy which divided the Muslim political elite into two groups; those who supported the President's proposal and those who opposed it.DOI: 10.15408/sdi.v13i1.574